Toxicogenomics of nanoparticulate delivery of etoposide: potential impact on nanotechnology in retinoblastoma therapy - Mitra, Moutushy (Cancer Nanotechnol, 2010)
To develop a suitable formulation with high entrapment efficiency, etoposide-loaded poly(lactide-co-glycolide) nanoparticles (NPs) were formulated by single emulsion-solvent evaporation method by changing different formulation parameters such as drug loading, choice of organic solvent and percentage of emulsifier polyvinyl alcohol. The NPs showed higher entrapment efficiency, ~86% (with 15% (w/w) drug loading). The physicochemical parameters revealed smooth topology with size range (240–320 nm), a negative zeta potential (~19 mV) and in vitro sustained-release activity (~60% drug release in 40 days). Greater anti-proliferative activity ~100 times was observed with NPs (IC(50) = 0.002 μg/ml) than that of native etoposide (IC(50) = 0.2 μg/ml) in retinoblastoma cell line (Y-79). These NPs demonstrated greater (G1/S) blocking and decreased mitochondrial membrane potential as measured by flow cytometry. There was upregulation of apoptotic gene activity in NPs than native etoposide, as revealed through microarray analysis. However, this is the first ever report demonstrating the intricate modulation of genetic network affected by NPs. Collectively, these results suggest that etoposide-loaded NPs could be potentially useful as a novel drug delivery system for retinoblastoma in the future. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12645-010-0010-4) contains supplementary material, which is available to authorized users.